Equity in higher education: experience from a special program for admission to health careers - Gaete, Verónica; Sáenz, Pablo; de la Fabián, Rodrigo; Las Heras, Jorge; Riquelme, Gloria; Navarro, José; López, Carolina (Revista Chilena de Salud Pública, 2007)
Purpose: To describe the results from the first 5 years of a differentiated admission program designed for outstanding students of low socioeconomic income admitted to health careers of the Faculty of Medicine, University of Chile. Materials and Methods: Annually, 10 to 20 low-income-students from 3rd and 4th years of secondary school entered the program in virtue of their academic and psychosocial background. For one or two years, they received extra support in scientific subjects and abilities for life, tutoring and vocational guidance. They also took the PAA/PUU (general post-secondary school test). Of the students who succeeded the pre-selection, up to 5 per year were chosen for admission to University according to their academic and vocational background and their psychosocial adaptation conditions. They studied their careers under full bursary coverage and other financial supports. Those who failed admission were helped to access other instances of higher education. Results: To date, 57 students have participated in the program. Of these, 43,9% are females and 56,1% are men. Their average secondary school grade was x = 6,1. In total, 43,5% had no prior expectations on being admitted to university. During the initial support delivery, 41,1% evidenced a lack of study habits and techniques, 33,3% showed a psychopathological condition and 38,6% evidenced risk behaviors. In 15,8% of the cases students dropped out and in 17,5% there was student exclusion. Drop out was due mainly to vocational problems and stress, and exclusion was due to low performance and psychopathological conditions. Of the students who completed the previous stage, 47,4% was selected to study careers at the Faculty. Their test scores were below the minimum for regular admission. In general, their subsequent performance was satisfactory. Conclusions: The program generated university access opportunities that were beyond the expectations of this group of youngsters. Their psychosocial facts hindered their performance. The support in this area is very significant for this kind of program. Students performance within the Faculty was satisfactory in spite of the fact they wouldn't have been admitted through the regular admission process. A widening of selection criteria for low-income students is necessary to generate equity in university education.